The Impact of an Early Eclectic Rehabilitative Intervention on Symptoms in First Episode Depression among Employed People. (10th November 2013) - Raiskila, Tero; Blanco Sequeiros, Sanna; Kiuttu, Jorma; Kauhanen, Marja-Liisa; Läksy, Kristian; Vainiemi, Kirsi; Tuulio-Henriksson, Annamari; Hakko, Helinä; Joukamaa, Matti; Veijola, Juha
Abstract : Objective . To evaluate the effect of an early vocational-orientated eclectic intervention on beck depression inventory (BDI) scores compared to treatment as usual in first ever depressive episode among employed people. Design . A randomized controlled trial comparing the rehabilitative intervention and the conventional treatment. Subjects . The subjects came from occupational health care units. Methods . Employees were sent to a rehabilitation center after being screened for depression using the BDI. They were diagnosed using the structured clinical interview for DSM-IV. The participating subjects (N = 283 ) were randomized into intervention and control groups. The intervention group received eclectic early depression intervention treatment (N = 134 ) and the control group was treated in the conventional way (N = 100 ). They were followed for one year. Results . The mean decrease in BDI scores within the intervention group was from 20.8 to 11.6 and within the control group from 19.3 to 10.8. BDI score decreased by 10 or more points in 64% of the participants in the intervention group and in 53% of the control group (P = 0.013 ). Conclusions . There was some evidence that early eclectic intervention in first ever episode depression may be more effective than conventional treatments among working age people in employment.